Financial liberalisation and credit dynamics in Denmark in the post-world war II period - Kim Abildgren (Danmarks Nationalbank, 2007)
Long-span time series on credit by institutional sectors and industries are not readily available in Denmark. The paper constructs annual time series for credit to Danish residents by sector and industry 1951-2005 and explores the trends and cycles in credit during the past five decades. There seems to have been a structural shift in the relationship between growth in real credit and economic activity around 1980 that might be related to the development in the monetary and financial system broadly defined. In the post-1980 period characterised by increased influence from market forces due to financial liberalisation and internationalisation the swings in real credit growth have been very large relative to the economic growth compared to the pre-1980 period where credit rationing and exchange controls served as important economicpolicy instruments. The credit expansion during the last five decades has caused an upward trend in loan-tovalue ratios. However, throughout the entire period the macro level of non-financial sector indebtedness relative to the stock of real assets and net financial assets has been fairly low, even after the house price decline during the late 1980s and early 1990s. The process of financial liberalisation in Denmark has therefore been relatively smooth and has not raised any concern regarding financial stability seen from a macroeconomic point of view. There seems to have been a shift over time in the short-term cyclical behaviour of commercial credit to the various industries. Real credit to agriculture, industry and services were contemporaneous with private sector real GDP in the pre-1980 period but has lagged the business cycle with one year in the post-1980 period. This might reflect the more restricted access to credit in the pre-1980 period, which gave firms an incentive to raise loans at an early stage of the business cycle in order to be sure to have command over the funding necessary for their planned investments. Another possible explanation could be the increased significance of commercial and industrial foundations in the Danish economy. Foundations might be seen as patient owners without an urgent need for return on equity. In step with the increased capital accumulation in those foundations it might therefore have been possible for Danish firms to finance larger shares of their fixed investments in the initial stages of an upturn with own funds from retained earnings rather than loans from domestic and foreign credit institutes.
Keywords: C82; E51; G21; N24; 330; bank-lending data; credit growth; financial liberalisation; financial stability; credit dynamics; business cycles; band-pass filter; Finanzsektor; Kreditgeschäft; Konjunktur; Zeitreihenanalyse; Bankgeschichte; Dänemark